EFFECT OF MONDAY THURSDAY FASTING ON WORKING MEMORY AFTER ACUTE STRESS EXPOSURE - Abdullah Faqih; Sinu Andhi Jusup; Nanang Wiyono; Isna Qadrijati (International Journal of Islamic and Complementary Medicine, 2023)
Working memory is part of cognitive function relates to the learning process and associates human behavior with the nervous system. Stress can cause a disruption to the body's homeostasis system. Monday-Thursday fasting can be used to counter the negative effects of stress by inhibiting stress mediators pathways. This study aims to prove that monday-thursday fasting can maintain working memory function after getting acute stress.  This study was quasi experimental with post test only control group design in 124 medical  students of  Sebelas Maret University, aged 18-25 years, normal BMI, and not taking corticosteroid or psychopharmaceutical drugs. Samples were taken by purposive sampling method divided into 4 groups. The control did not get treatment, treatment group 1 (TG1) was given acute stress induction in the form of academic examinations, sing a song stress test (SSST), and arithmetic test, treatment group 2 (TG2) carried out fasting at least 3 months and was given acute stress induction. Dependent variables are Monday-thursday fasting and acute stressors in the form of nominal categorical data. Independent variables in the form of working memory measured using digit-span tests in the form of numerical-interval data. Measurements of working memory were carried out simultaneously in the tutorial room after each group received treatment. Working memory data were analyzed by MANOVA and Bonferroni tests (a = 0.05). The highest working memory is found in TG2 followed by control, and TG1. The results of the MANOVA test showed significant differences between the four groups with p = 0,000. The Bonferroni test results show significant differences between the control-TG1 and TG1-TG2 with each p <0.05. Fasting on Mondays-Thursdays activity can maintain a working memory function when the body gets acute stress.